THE CONCEPT OF TEACHING READING AND DEVELOPMENT OF READING SUB-SKILLS - DJOKO ARDHITYAWAN; SUWARNO - (Fakultas Sastra Universitas Gresik, 2016)
This research concerned in the applying concept of teaching reading and development of reading sub-skills. There are many sub-skills in reading comprehenshion, in this case the researcher only focused on seven kinds of sub-skills in reading. The most important thing to bear in mind while designing materials on reading class is that teachers must be sure that the task given to their students to develop the reading sub skill as written in their lesson plan (the objectives). The three phase technique may be followed. The more important thing, however, is the development of the reading sub skills themselves.